2010
DOI: 10.1590/s0104-11692010000600018
|View full text |Cite
|
Sign up to set email alerts
|

The Active Search for Respiratory Symptomatics for the Control of Tuberculosis in the Potiguara Indigenous Scenario, Paraiba, Brazil

Abstract: This study sought to analyze the actions of an active search for respiratory symptomatics (RSs) in the control of tuberculosis (TB) enfermagem e agentes indígenas de saúde. Utilizou-se a técnica de grupo focal como instrumento de coleta de dados, cujo tratamento fundamentou-se na técnica de análise de discurso. Evidenciaram-se debilidades de natureza operacional, relacionadas à organização do serviço de saúde local para a implantação de rotinas de diagnóstico para a TB: ausência de rotina sistematizada para … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
(30 reference statements)
0
6
0
4
Order By: Relevance
“…However, our results are consistent with the findings of a study conducted in two cities in Colombia by Daza Arana (2013), which concluded that living in poor housing with inadequate ventilation and in homes with roofs predominantly made of waste material were associated with an increased prevalence of RS (Moreno & Peña 2010). In addition, research conducted in Bucaramanga, Colombia (Nóbrega et al 2010) found that RS was associated with households with no windows, with occupancies > 3 people per room, and a floor predominantly made of cement. This finding is consistent with the study by Krieger and Higgins, who reported that poor housing conditions were associated with health conditions, including the transmission of TB (Krieger & Higgins 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results are consistent with the findings of a study conducted in two cities in Colombia by Daza Arana (2013), which concluded that living in poor housing with inadequate ventilation and in homes with roofs predominantly made of waste material were associated with an increased prevalence of RS (Moreno & Peña 2010). In addition, research conducted in Bucaramanga, Colombia (Nóbrega et al 2010) found that RS was associated with households with no windows, with occupancies > 3 people per room, and a floor predominantly made of cement. This finding is consistent with the study by Krieger and Higgins, who reported that poor housing conditions were associated with health conditions, including the transmission of TB (Krieger & Higgins 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic status and educational level may influence care seeking and attendance at health services. A study in Brazil found that barriers to access to health services in indigenous population influenced the presence of RS, as individuals were less likely to seek medical care (Nóbrega et al 2010). In our study, the types of housing and home heating increased the risk of having symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…A higher number of negative results in the bacilloscopies of the 1st and 2nd sputum samples was observed in the indigenous population, which could be partly explained by inadequate orientation of the patient at the time of sample collection or—as proposed by recent studies—by inappropriate storage and transport of the samples and technical incompetence resulting in incorrect reading of the sputum smears [ 25 , 28 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…As well as addressing the day-to-day practices of direct nursing care to patients, families and vulnerable groups, we highlight the need for nurses in previous care planning, identifying the vulnerable groups for TB disease within the community and then perform active case identification Melo and Campinas, 2010;Nobrega et al, 2010), to increase case detection rates among the population.…”
Section: Ijrnmentioning
confidence: 99%